KOLABORASI PERAN MASYARAKAT DAN PEMERINTAH DESA DALAM PEMBANGUNAN DI DESA SUKAMANAH KECAMATAN CIBEBER KABUPATEN CIANJUR - Ervin Rahayu Gumilar; Fadila Khaerunnisa; Fitri Lutfiah; Hayyi Itqi Tammi; Jaliluddin Jaliluddin (Jurnal Inovasi Penelitian, 2021)
In developing a village, collaboration between ecological actors of public administration is needed. What is meant in this case is the government and society. The success of a development is very dependent on the support from the community and government. Development programs in Sukamanah Village will not be successful if there is no collaboration from the government and the people of Sukamanah Village. The purpose of this paper was to determine the collaboration of ecological public administration actors in Sukamanah Village and describe about cooperation between actors in village development. This study used a qualitative descriptive research method with data collection through observation, interviews and library research. The results showed that there was collaboration between the government and local communities in carrying out development. Not all communities are involved in village development, only representatives are elected to be development administrators. Until now, the development of Sukamanah village has been running smoothly and there are several programs that have not been implemented.